(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the evolution and application of business strategy in today’s dynamic and competitive environment. It outlines classical and contemporary strategic frameworks, discusses the process of strategy formulation and execution, and explores the drivers of sustainable competitive advantage. By integrating insights from resource‐based, positioning, and dynamic capabilities perspectives, the article provides a holistic understanding of how firms can adapt and thrive amid technological disruption, globalization, and shifting stakeholder expectations.